Penerapan Lesson Study Pada Perkuliahan Struktur Aljabar 1 - Tafsillatul Mufida Asriningsih (Sekolah Tinggi Agama Islam At-Tahdzib Ngoro Jombang Indonesia, 2017)
This research is a qualitative descriptive research, with the aim to describe the application of lesson study in the lecture of Structure Algebra 1. The implementing team of lesson study consists of six lecturers model. The subjects of the study were 32 students of the participants of the Algebraic Structure Course I Academic Year 2013/2014. Lesson study is applied to the planning (plan), implementation (do), and reflection (see) phases implemented in three cycles. Based on the results of reflection at the stage of the 1st, found problems at the stage of lecturing that some activities do not take place effectively. This ineffectiveness appears in apperception, group discussion, and student presentations. As a result, the implementation time of the activity is longer than planned. This problem is no longer visible in the 2nd as a result of the 1st reflection. Although generally show improvement of lecture activity, but still found problem that is lack of understanding of student concept. So in the 3rd do a review related all the materials that have been studied in this lesson study. Based on the discussion of the implementation of the lesson study, the lecture structure of Algebra 1 has improved in the implementation phase in every cycle.